Subjective memory complaints, depressive symptoms and cognition in patients attending a memory outpatient clinic. (5th December 2013) - Lehrner, J.; Moser, D.; Klug, S.; Gleiß, A.; Auff, E.; Dal-Bianco, P.; Pusswald, G.
ABSTRACT: Background: The goals of this study were to establish prevalence of subjective memory complaints (SMC) and depressive symptoms (DS) and their relation to cognitive functioning and cognitive status in an outpatient memory clinic cohort. Methods: Two hundred forty-eight cognitively healthy controls and 581 consecutive patients with cognitive complaints who fulfilled the inclusion criteria were included in the study. Results: A statistically significant difference (p < 0.001) between control group and patient group regarding mean SMC was detected. 7.7% of controls reported a considerable degree of SMC, whereas 35.8% of patients reported considerable SMC. Additionally, a statistically significant difference (p < 0.001) between controls and patient group regarding Beck depression score was detected. 16.6% of controls showed a clinical relevant degree of DS, whereas 48.5% of patients showed DS. An analysis of variance revealed a statistically significant difference across all four groups (control group, SCI group, naMCI group, aMCI group) (p < 0.001). Whereas 8% of controls reported a considerable degree of SMC, 34% of the SCI group, 31% of the naMCI group, and 54% of the aMCI group reported considerable SMC. A two-factor analysis of variance with the factors cognitive status (controls, SCI group, naMCI group, aMCI group) and depressive status (depressed vs. not depressed) and SMC as dependent variable revealed that both factors were significant (p < 0.001), whereas the interaction was not (p = 0.820). Conclusions: A large proportion of patients seeking help in a memory outpatient clinic report considerable SMC, with an increasing degree from cognitively healthy elderly to aMCI. Depressive status increases SMC consistently across groups with different cognitive status.